Biocatalytic enantioselective formation and ring-opening of oxetanes - Xia Hua; Yuan-Fei Wang; Xiao Jin; Hong-Yin Yu; Hui-Hui Wang; Yong-Zheng Chen; Nan-Wei Wan (Nature Communications)
Abstract Although biocatalysis offers complementary or alternative approaches to traditional synthetic methods, the limited range of available enzymatic reactions currently poses challenges in synthesizing a diverse array of desired compounds. Consequently, there is a significant demand for developing novel biocatalytic processes to enable reactions that were previously unattainable. Herein, we report the discovery and subsequent protein engineering of a unique halohydrin dehalogenase to develop a biocatalytic platform for enantioselective formation and ring-opening of oxetanes. This biocatalytic platform, exhibiting high efficiency, excellent enantioselectivity, and broad scopes, facilitates the preparative-scale synthesis of chiral oxetanes and a variety of chiral γ-substituted alcohols. Additionally, both the enantioselective oxetane formation and ring-opening processes are proven scalable for large-scale transformations at high substrate concentrations, and can be integrated efficiently in a one-pot, one-catalyst cascade system. This work expands the enzymatic toolbox for non-natural reactions and will promote further exploration of the catalytic repertoire of halohydrin dehalogenases in synthetic and pharmaceutical chemistry.